Toner and method for producing the same

JP7638744B2Active Publication Date: 2025-03-04CANON KK
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2021045545
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-19
Publication Date
2025-03-04
Estimated Expiration
2041-03-19

AI Technical Summary

Benefits of technology

【0007】 本開示によれば、低温定着性と定着分離性を両立したトナーを提供できる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638744000001
    Figure 0007638744000001
  • Figure 0007638744000002
    Figure 0007638744000002
  • Figure 0007638744000003
    Figure 0007638744000003
Patent Text Reader

Abstract

To provide a toner that can achieve both low temperature fixability and separability during fixing.SOLUTION: A toner has a toner particle containing a binder resin and a mold release agent. The binder resin contains a first resin and a second resin. The first resin is a crystalline resin having a melting point Tp of 50°C or more and 90°C or less. The second resin is an amorphous resin. On a cross section of the toner particle observed by a transmission electron microscope, a matrix-domain structure is present which consists of a matrix including the first resin and domains including the second resin. In the total area of the cross section of the toner particle, the ratio of the area occupied by the matrix including the first resin is 35 area% or more and 70 area% or less. When the direction of the longest domain is a longitudinal direction, the standard deviation of the angle in the longitudinal direction of the domain is 25° or less.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to a toner used in electrophotography, electrostatic recording, electrostatic printing, toner jet printing, and the like, and a method for producing the toner. [Background technology]

[0002] In recent years, as full-color electrophotographic copiers have become more widespread, there has been an ever-increasing demand for faster printing and energy conservation. To accommodate high-speed printing, technology that melts toner more quickly in the fixing process is being considered. Also, to improve productivity, technology that shortens the time for various controls during a job and between jobs is being considered. Also, as an energy-saving measure, technology that fixes toner at a lower temperature is being considered in order to reduce power consumption in the fixing process.

[0003] It is known that a toner having a binder resin mainly composed of a crystalline resin having sharp melting properties has excellent low-temperature fixing properties compared to a toner having an amorphous resin as the main component. For example, Patent Document 1 describes a toner in which a domain matrix structure is formed having a matrix containing a crystalline resin and a domain containing an amorphous resin and a colorant, and the domain diameter and storage modulus are set within a predetermined range. This allows a toner having excellent fixing properties, image density, and image glossiness to be obtained. Patent Document 2 describes a toner in which a domain matrix structure is formed having a matrix containing a crystalline resin in a predetermined melting point range and a domain containing an amorphous resin. This allows a toner to be fixed with low energy and to obtain an image that is resistant to external forces such as rubbing and scratching. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2014-059489 A [Patent Document 2] JP 2014-142632 A Summary of the Invention [Problem to be solved by the invention]

[0005] The toner described in the above document has a domain matrix structure, and a crystalline resin having sharp melting properties forms the matrix, so that the toner has excellent fixing properties at low energy. On the other hand, it has been found that under certain conditions, the migration of the release agent to the image surface during fixing may be insufficient, and the fixing separation properties may be reduced. The present disclosure is directed to a toner that can achieve both low-temperature fixing properties and fixing separation properties. [Means for solving the problem]

[0006] A toner having toner particles containing a binder resin and a release agent, The binder resin contains a first resin and a second resin, The first resin is a crystalline resin having a melting point Tp of 50° C. or more and 90° C. or less, the second resin is an amorphous resin, In a cross section of the toner particle observed by a transmission electron microscope, a matrix domain structure is present that is composed of a matrix containing the first resin and a domain containing the second resin, an area ratio of the matrix containing the first resin to the total area of ​​the cross section of the toner particle is 35 area % or more and 70 area % or less; The toner is characterized in that, when the longest direction of the domain is taken as the longitudinal direction, the standard deviation of the angle of the longitudinal direction of the domain is 25° or less. Effect of the Invention

[0007] According to the present disclosure, a toner that achieves both low-temperature fixability and fixation separation property can be provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] In the present disclosure, the description of "XX or more and YY or less" or "XX to YY" representing a numerical range means a numerical range including the lower and upper limits which are the endpoints, unless otherwise specified. (Meth)acrylic acid ester means acrylic acid ester and / or methacrylic acid ester. When a numerical range is described in stages, the upper and lower limits of each numerical range can be arbitrarily combined. "Monomer unit" refers to the reacted form of a monomer substance in a polymer. For example, one section of a carbon-carbon bond in the main chain in which a vinyl monomer in a polymer is polymerized is considered to be one unit. A vinyl monomer can be represented by the following formula (Z). [ka]

[0009] In formula (Z), R Z1 represents a hydrogen atom or an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group), R Z2 represents an optional substituent. The crystalline resin refers to a resin that shows a clear endothermic peak in a differential scanning calorimeter (DSC) measurement.

[0010] The present disclosure relates to a toner having toner particles containing a binder resin and a release agent, The binder resin contains a first resin and a second resin, The first resin is a crystalline resin having a melting point Tp of 50° C. or more and 90° C. or less, the second resin is an amorphous resin, In a cross section of the toner particle observed by a transmission electron microscope, a matrix domain structure is present that is composed of a matrix containing the first resin and a domain containing the second resin, an area ratio of the matrix containing the first resin to the total area of ​​the cross section of the toner particle is 35 area % or more and 70 area % or less; The toner relates to a toner in which, when the longest direction of the domain is defined as the longitudinal direction, the standard deviation of the angle of the longitudinal direction of the domain is 25° or less.

[0011] As a result of extensive research, the inventors have found that the above-mentioned problem can be solved by forming a domain matrix structure consisting of a matrix containing a first resin, which is a crystalline resin having a predetermined melting point, and a domain containing a second resin, which is an amorphous resin, and by controlling the area occupied by the first resin in the cross section of the toner particle and the orientation state of the domain.

[0012] The inventors speculate that the reason for solving the above problem is as follows. First, by using a crystalline resin having a melting point Tp of 50°C or more and 90°C or less, which has excellent sharp melting properties at low energy, and forming a matrix domain structure consisting of a matrix containing a first resin and a domain containing a second resin, excellent low-temperature fixability can be obtained. When there is no domain matrix structure and the first resin and the second resin are compatible with each other to form a uniform structure, the fixation separation property is likely to decrease. Furthermore, the sharp melting property of the crystalline resin is likely to be lost and the low-temperature fixability is likely to decrease. The melting point Tp is preferably 55°C or more and 70°C or less.

[0013] On the other hand, for good fixing separation, it is important that the release agent dispersed in the toner particles migrates to the toner particle surface during fixing and is present between the toner image surface and the fixing roller. In the toner having a risk domain structure, it is believed that during fixing, the release agent migrates to the surface of the toner particles via the matrix containing the first resin.

[0014] Therefore, when the orientation state of the domain containing the second resin is irregular, it is considered that the migration of the release agent to the toner particle surface is hindered. Therefore, it is considered that the migration of the release agent to the toner particle surface during fixing can be promoted by aligning the orientation of the domain containing the second resin. As a result of the investigation, it was found that the migration of the release agent to the toner particle surface can be promoted by setting the standard deviation of the longitudinal angle of the domain to 25° or less, and good fixing separation properties can be obtained. The standard deviation of the longitudinal angle of the domain is preferably 22° or less. The lower limit is not particularly limited, but is preferably 1° or more, more preferably 5° or more, and even more preferably 10° or more.

[0015] This effect can be obtained when the area ratio of the matrix containing the first resin to the total area of ​​the cross section of the toner particle is in the range of 35 area % or more and 70 area % or less. When the area ratio of the matrix containing the first resin is less than 35 area %, the above-mentioned matrix domain structure is reversed, and a matrix domain structure consisting of a matrix containing the second resin and a domain containing the first resin may be formed, resulting in a decrease in low-temperature fixability. On the other hand, when the area ratio of the matrix containing the first resin is more than 70 area %, the viscosity of the matrix containing the molten first resin is likely to be low during high-temperature fixation, and the fixation separation property is likely to be decreased.

[0016] In addition, the area ratio of the matrix containing the first resin to the total area of ​​the cross section of the toner particle is preferably 40 area % or more and 60 area % or less. As described above, it is considered that the release agent migrates to the toner particle surface via the matrix containing the first resin, so if the area ratio of the matrix containing the first resin is 60% or less, the density of the domain containing the second resin increases, and the fixing separation property is easily improved. In addition, the area ratio of the matrix containing the first resin to the total area of ​​the cross section of the toner particle can be controlled by the amount of the first resin and the second resin charged.

[0017] The softening temperature Tm of the second resin is preferably higher than the melting point Tp of the first resin by 10° C. or more. When the softening temperature Tm of the second resin approaches the melting point of the first resin, the difference in viscosity between the first resin and the second resin becomes small during fixing, so that the release agent migrates to the second resin side forming the domain, and migration to the toner particle surface is inhibited.

[0018] Therefore, in order to facilitate the transfer of the release agent to the toner particle surface and improve the fixing separation property, it is considered that the softening temperature Tm of the second resin is set to be 10°C or more higher than the melting point Tp of the first resin, so that the release agent can be easily transferred to the toner particle surface via the matrix containing the first resin. The softening temperature Tm of the second resin can be controlled by the molecular weight of the amorphous resin contained in the second resin. By increasing the molecular weight, the softening temperature Tm of the second resin can be increased. More preferably, the softening temperature Tm of the second resin is Tp+20°C or more and Tp+50°C or less.

[0019] In the cross-sectional observation of the toner particle, the average length (average major axis) of the domain in the longitudinal direction is preferably 20 nm or more and 500 nm or less. When the average major axis of the domain is 500 nm or less, the second resin is easily melted even during low-temperature fixing of the toner, and the fixing property is improved. On the other hand, during high-temperature fixing, the viscosity of the matrix containing the melted first resin is unlikely to decrease, and the fixing separation property is improved. In addition, when the average major axis of the domain is 20 nm or more, the fixing separation property is improved, and the sharp melt property of the crystalline resin is easily exhibited, and the low-temperature fixing property is improved. The average length of the domain in the longitudinal direction is more preferably 80 nm or more and 430 nm or less.

[0020] The average major axis of the domains can be controlled by the composition of the monomers constituting the crystalline resin, the composition of the monomers constituting the amorphous resin, the manufacturing conditions of the toner particles, etc. Methods for controlling the average major axis of the domains include the relationship between the SP values ​​of the resins constituting the matrix and the domains, the kneading temperature and screw rotation speed in the melt kneading process, and the stirring rotation speed in the aggregation process. If the SP values ​​of the matrix and domain resins are close to each other, the compatibility between the matrix and the domains increases, and the average major axis of the domains tends to become smaller. Furthermore, increasing the screw rotation speed or stirring rotation speed increases the shear force on the resin, and the average major axis of the domains becomes smaller.

[0021] The ratio La / Lb of the domain's length in the longitudinal direction La to the maximum length Lb in the direction perpendicular to the longitudinal direction is preferably 8.0 or less, more preferably 5.5 or less. There is no particular lower limit, but it is preferably 1.1 or more, more preferably 1.5 or more.

[0022] A large ratio La / Lb indicates that the surface area of ​​the domain is larger than that of a sphere of the same volume, that is, the contact area between the matrix and the domain is large. In other words, it is considered that the matrix containing the first resin and the domain containing the second resin are easily compatible with each other. The toner has a high effect when the matrix containing the first resin and the domain containing the second resin are functionally separated. Therefore, by setting the ratio La / Lb to 8.0 or less, the fixing separation property is further improved. The ratio La / Lb can be controlled by adjusting the SP value of the first resin contained in the matrix and the second resin contained in the domain. The ratio La / Lb can be reduced by increasing the difference in the SP value between the two.

[0023] Usable materials are described in detail below. <First Resin> The binder resin contains a first resin, and the first resin is a crystalline resin. As the crystalline resin, a known crystalline resin can be used. For example, a crystalline vinyl resin, a crystalline polyester resin, a crystalline polyurethane resin, and a crystalline polyurea resin can be mentioned. In addition, ethylene copolymers such as ethylene-vinyl acetate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-methyl methacrylate copolymer, ethylene-methacrylic acid copolymer, and ethylene-acrylic acid copolymer can also be mentioned.

[0024] From the viewpoint of low-temperature fixability, crystalline vinyl resin and crystalline polyester resin are preferred. Also, it may be a hybrid resin in which a vinyl resin and a polyester resin are bonded. The first resin preferably contains a vinyl resin, more preferably is a vinyl resin, and preferably has a first monomer unit represented by the following formula (1). The first resin is preferably a vinyl resin having a monomer unit represented by the following formula (1). The vinyl resin is a polymer or copolymer of a compound containing a group having an ethylenically unsaturated bond such as a vinyl group. Examples of the group having an ethylenically unsaturated bond include a vinyl group, a (meth)allyl group, and a (meth)acryloyl group.

[0025] The content of the first monomer unit in the first resin is preferably 30.0 mass % to 90.0 mass %, more preferably 45.0 mass % to 75.0 mass %. The weight average molecular weight (Mw) of the first resin is preferably 5,000 to 100,000, more preferably 15,000 to 50,000. [ka]

[0026] In formula (1), R Z1 represents a hydrogen atom or a methyl group, R 1 represents an alkyl group having 18 to 36 carbon atoms. The first monomer unit represented by the above formula (1) has R 1The presence of this moiety facilitates the development of crystallinity. The first monomer unit represented by formula (1) is preferably a monomer unit derived from at least one first polymerizable monomer selected from the group consisting of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms.

[0027] Examples of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms include (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosanyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate, octacosyl (meth)acrylate, myrisyl (meth)acrylate, dotriacontyl (meth)acrylate, etc.] and (meth)acrylic acid esters having a branched alkyl group having 18 to 36 carbon atoms [2-decyltetradecyl (meth)acrylate, etc.].

[0028] Among these, from the viewpoint of low temperature fixability, at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group with 18 to 36 carbon atoms is preferable, at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group with 18 to 30 carbon atoms is more preferable, and at least one selected from the group consisting of linear stearyl (meth)acrylate and behenyl (meth)acrylate is even more preferable. The monomers forming the first monomer unit may be used alone or in combination of two or more kinds.

[0029] SP value of the first monomer unit (J / cm 3 ) 0.5 is SP1, SP1 is preferably less than 20.00, more preferably 19.00 or less, and even more preferably 18.40 or less. The lower limit is not particularly limited, but is preferably 17.00 or more.

[0030] Here, the SP value is an abbreviation for solubility parameter, and is a value that serves as an index of solubility. The calculation method will be described later. The unit of the SP value is (J / cm 3 ) 0.5 However, 1 (cal / cm 3 ) 0.5 =2.045×10 3 (J / cm 3 ) 0.5 by (cal / cm 3 ) 0.5 can be converted to units of

[0031] The first resin preferably has a second monomer unit different from the first monomer unit, which is at least one selected from the group consisting of monomer units represented by the following formula (2) and the following formula (3). The SP value of the second monomer unit is SP2 (J / cm 3 ) 0.5 When the above formula (4) is satisfied, it is preferable that the following formula (4') is satisfied. It is more preferable that the following formula (4') is satisfied. There is no particular upper limit for SP2, but it is preferably 30. 00 or less. 21.00 (J / cm 3 ) 0.5 ≦SP2 (4) 25.00 (J / cm 3 ) 0.5 ≦SP2···(4´)

[0032] When the SP2 of the second monomer unit satisfies the above formula (4), the second monomer unit has high polarity, and a polarity difference occurs between the first and second monomer units. This polarity difference promotes crystallization of the first monomer unit, thereby obtaining excellent low-temperature fixability. Specifically, the first monomer unit is incorporated into a crystalline resin, and the first monomer units aggregate with each other to exhibit crystallinity.

[0033] Usually, the crystallization of the first monomer unit is inhibited when other monomer units are incorporated, making it difficult for the first monomer unit to exhibit crystallinity as a crystalline resin. However, by setting the SP1 of the first monomer unit and the SP2 of the second monomer unit within the above-mentioned range, it is believed that the first monomer unit and the second monomer unit can form a clear phase-separated state in the first resin without being miscible with each other, and it is believed that the melting point can be easily maintained without reducing the crystallinity. [ka]

[0034] (In formula (2), X represents a single bond or an alkylene group having 1 to 6 carbon atoms. R 3 is -C≡N, -C(=O)NHR 10 (R 10 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms; Hydroxy groups, -COOR 31 (R 31 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4), or a hydroxyalkyl group having 1 to 6 carbon atoms (preferably 1 to 4), -NH-C(=O)-N(R 33 )2(Two R 33 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4 carbon atoms), -COO(CH2)2NHCOOR 34 (R 34 represents an alkyl group having 1 to 4 carbon atoms, or -COO(CH2)2-NH-C(=O)-N(R 35 )2(Two R 35 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms (preferably 1 to 4). R 4 represents a hydrogen atom or a methyl group. [ka]

[0035] (In formula (3), R 5 represents an alkyl group having 1 to 4 carbon atoms, R 6 represents a hydrogen atom or a methyl group. Specific examples of the second polymerizable monomer that forms the second monomer unit include the following polymerizable monomers. Preferably, a polymerizable monomer that can form the monomer unit represented by the above formula (2) or (3) is used. Monomers having a nitrile group; for example, acrylonitrile, methacrylonitrile, etc. Monomers having a hydroxy group; for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and the like.

[0036] Monomers having an amide group; for example, acrylamide, monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 2 to 30 carbon atoms (acrylic acid, methacrylic acid, etc.) having an ethylenically unsaturated bond by a known method.

[0037] Monomer having a urea group: for example, a monomer obtained by reacting an amine having 3 to 22 carbon atoms [primary amine (normal butylamine, t-butylamine, propylamine, isopropylamine, etc.), secondary amine (di-normal ethylamine, di-normal propylamine, di-normal butylamine, etc.), aniline, cycloxylamine, etc.] with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond by a known method, etc. Monomers having a carboxy group; for example, methacrylic acid, acrylic acid, 2-carboxyethyl (meth)acrylate.

[0038] Among them, it is preferable to use a monomer having a nitrile group, an amide group, a hydroxy group, or a urea group. More preferably, it is a monomer having at least one functional group selected from the group consisting of a nitrile group, an amide group, a hydroxy group, and a urea group, and an ethylenically unsaturated bond. Acrylonitrile and methacrylonitrile are particularly preferable.

[0039] Also preferably used as the second monomer unit are vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate, and vinyl octylate. Among these, vinyl esters are preferred from the viewpoint of low-temperature fixability because they are non-conjugated monomers and therefore tend to maintain a suitable reactivity with the first polymerizable monomer and tend to increase the crystallinity of the polymer.

[0040] The content of the second monomer unit in the first resin is preferably 5.0% by mass to 40.0% by mass, and more preferably 7.0% by mass to 30.0% by mass.

[0041] Within the range not impairing the mass ratio of the first monomer unit and the second monomer unit described above. and may contain a third monomer unit formed by polymerization of a third polymerizable monomer not falling within the scope of the above formula (4) (i.e., different from the first polymerizable monomer and the second polymerizable monomer). As the third polymerizable monomer, a monomer not satisfying the above formula (4) can be used among the monomers exemplified as the above second polymerizable monomer.

[0042] For example, the following monomers can also be used: styrene and its derivatives such as styrene and o-methylstyrene, and (meth)acrylic acid esters such as methyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate. Among these, the third polymerizable monomer is preferably styrene from the viewpoint of charge diffusion. The content of the third monomer unit in the first resin is preferably 5.0% by mass to 50.0% by mass, and more preferably 10.0% by mass to 35.0% by mass.

[0043] <Second resin> The binder resin contains a second resin, and the second resin is an amorphous resin. The second resin forming the domain can be a known amorphous resin, and is preferably a polyester resin, a styrene-acrylic resin, or a hybrid resin thereof from the viewpoint of low-temperature fixing property and fixing separation property. As the styrene-acrylic resin, a styrene-acrylic resin that is usually used in toners can be suitably used.

[0044] The second resin preferably contains a styrene-acrylic resin, and more preferably is a styrene-acrylic resin. The styrene-acrylic resin is preferably a copolymer of a styrene-based monomer and a (meth)acrylic monomer. The weight average molecular weight (Mw) of the second resin is preferably 10,000 to 100,000, and more preferably 20,000 to 60,000.

[0045] Examples of styrene monomers include styrene, α-methylstyrene, β-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, pn-dodecylstyrene, p-methoxystyrene, and p-phenylstyrene. These styrene monomers can be used alone or in combination.

[0046] Examples of the (meth)acrylic monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, iso-propyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-amyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, dimethyl phosphate ethyl (meth)acrylate, diethyl phosphate ethyl (meth)acrylate, dibutyl phosphate ethyl (meth)acrylate, and 2-benzoyloxyethyl (meth)acrylate, (meth)acrylonitrile, 2-hydroxyethyl (meth)acrylate, (meth)acrylic acid, and maleic acid. These (meth)acrylic monomers can be used alone or in combination.

[0047] As the polyester resin, a polyester resin that is usually used in a toner can be suitably used. The monomers used in the polyester resin include polyhydric alcohol (dihydric or trihydric or higher alcohol), polycarboxylic acid (dihydric or trihydric or higher carboxylic acid), and its acid anhydride or lower alkyl ester.

[0048] Examples of polyhydric alcohols include the following: Examples of dihydric alcohols include the following bisphenol derivatives: polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane, etc.

[0049] Other polyhydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerin, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene. These polyhydric alcohols can be used alone or in combination.

[0050] Examples of polyvalent carboxylic acids include the following. Examples of divalent carboxylic acids include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid, n-dodecylsuccinic acid, isododecylsuccinic acid, n-octenylsuccinic acid, n-octylsuccinic acid, isooctylsuccinic acid, isooctylsuccinic acid, anhydrides of these acids, and lower alkyl esters thereof. Of these, maleic acid, fumaric acid, terephthalic acid, and n-dodecenylsuccinic acid are preferably used.

[0051] Examples of trivalent or higher carboxylic acids, their acid anhydrides, and their lower alkyl esters include the following: 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, their acid anhydrides, and their lower alkyl esters.

[0052] Among these, 1,2,4-benzenetricarboxylic acid (trimellitic acid) or its derivatives such as anhydride are preferably used because they are inexpensive and the reaction can be easily controlled. These polyvalent carboxylic acids can be used alone or in combination.

[0053] <Other resins> The binder resin may contain a third resin other than the first resin and the second resin, for the purpose of improving pigment dispersibility, etc., to the extent that the effect of the present disclosure is not impaired. Examples of such resins include the following: polyvinyl chloride, phenolic resin, natural resin-modified phenolic resin, natural resin-modified maleic acid resin, polyvinyl acetate, silicone resin, polyester resin, polyurethane resin, polyamide resin, furan resin, epoxy resin, xylene resin, polyvinyl chloride ... Nylbutyral, terpene resins, coumarone-indene resins, petroleum-based resins.

[0054] <Release agent> The toner contains a release agent. It is advisable to select and use an optimal release agent in combination with the first resin and the second resin. It is considered that the release agent migrates to the toner particle surface via the first resin during fixing. Therefore, it is preferable that the melting point of the release agent is equal to or higher than the melting point Tp of the first resin and equal to or lower than the softening temperature Tm of the second resin. Examples of the release agent include the following. Note that wax is synonymous with release agent.

[0055] Hydrocarbon waxes such as low molecular weight polyethylene, low molecular weight polypropylene, alkylene copolymers, microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; waxes whose main component is fatty acid esters such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax.

[0056] Further examples include the following: saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and parinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene saturated fatty acid bisamides such as ethylene bisoleamide, hexamethylene bisoleamide, N,N'-dioleyl adipamide, N,N'-dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearyl isophthalamide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxy groups obtained by hydrogenation of vegetable oils and fats.

[0057] The release agent preferably contains a hydrocarbon wax, and the content of the wax is preferably 2.0 parts by mass to 30.0 parts by mass with respect to 100 parts by mass of the binder resin.

[0058] <Coloring agent> The toner particles may contain a colorant as required. Examples of the colorant include the following. Examples of the black colorant include carbon black, and a colorant toned to black using a yellow colorant, a magenta colorant, and a cyan colorant. As the colorant, a pigment may be used alone, but it is more preferable to use a dye and a pigment in combination to improve the clarity in terms of the image quality of a full-color image.

[0059] Pigments for magenta toner include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57: 1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35.

[0060] Dyes for magenta toners include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.

[0061] Pigments for cyan toner include: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45, copper phthalocyanine pigments with 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton. An example of a dye for cyan toner is CI Solvent Blue 70.

[0062] Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow toner dyes include CI Solvent Yellow 162.

[0063] These colorants can be used alone or in mixture, or in the form of a solid solution. The colorant is selected in terms of hue angle, chroma, brightness, light resistance, OHP transparency, and dispersibility in toner. The content of the colorant is preferably 0.1 to 30.0 parts by mass relative to 100 parts by mass of the binder resin.

[0064] <Charge control agent> The toner particles may contain a charge control agent as necessary. By blending a charge control agent, the charge characteristics can be stabilized, and the amount of triboelectric charge can be optimally controlled according to the development system. As the charge control agent, a known one can be used, but in particular, a metal compound of an aromatic carboxylic acid is preferred, which is colorless, has a high charging speed of the toner, and can stably maintain a constant amount of charge.

[0065] Examples of negative charge control agents include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes.

[0066] The charge control agent may be added internally or externally to the toner particles. The content of the charge control agent is preferably 0.2 parts by mass to 10.0 parts by mass, and more preferably 0.5 parts by mass to 10.0 parts by mass, based on 100 parts by mass of the binder resin.

[0067] <Inorganic fine particles> The toner may contain inorganic fine particles as required. The inorganic fine particles may be added internally to the toner particles, or may be mixed with the toner as an external additive. Examples of inorganic fine particles include silica fine particles, titanium oxide fine particles, alumina fine particles, and composite oxide fine particles thereof. Among the inorganic fine particles, silica fine particles and titanium oxide fine particles are preferred for improving flowability and uniform charging. The inorganic fine particles are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof.

[0068] From the viewpoint of improving fluidity, inorganic fine particles as external additives should have a specific surface area of ​​50 m 2 / g~400m 2 From the viewpoint of improving durability and stability, it is preferable that the inorganic fine particles as the external additive have a specific surface area of ​​10 m 2 / g~50m 2In order to achieve both improved fluidity and durability and stability, inorganic fine particles having a specific surface area within the above range may be used in combination.

[0069] The content of the external additive is preferably 0.1 parts by mass to 10.0 parts by mass with respect to 100 parts by mass of the toner particles. The toner particles and the external additive can be mixed using a known mixer such as a Henschel mixer.

[0070] <Developer> The toner can be used as a one-component developer, but it is more preferable to mix the toner with a magnetic carrier and use it as a two-component developer, in that stable images can be obtained over a long period of time.

[0071] Examples of magnetic carriers that can be used include generally known magnetic carriers such as iron powder with an oxidized surface, unoxidized iron powder, metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, and rare earth elements, alloy particles thereof, oxide particles, magnetic materials such as ferrite, and magnetic material-dispersed resin carriers (so-called resin carriers) that contain a magnetic material and a binder resin that holds the magnetic material in a dispersed state.

[0072] When the toner is mixed with a magnetic carrier to be used as a two-component developer, good results are usually obtained when the carrier mixing ratio, in terms of the toner concentration in the two-component developer, is preferably 2.0% by mass or more and 15.0% by mass or less, and more preferably 4.0% by mass or more and 13.0% by mass or less.

[0073] <Toner manufacturing method> The method for producing the toner is not particularly limited, and a known production method can be used. The melt-kneading / pulverization method is preferably used. The melt-kneading / pulverization method includes, for example, a melt-kneading step of melt-kneading a composition containing a binder resin and a release agent to obtain a melt-kneaded product, and a pulverization step of cooling and solidifying the melt-kneaded product, and pulverizing the cooled and solidified product to obtain a pulverized product.

[0074] In the above-mentioned manufacturing method, it is easy to apply shear stress to the melted and kneaded material immediately after the matrix domain structure composed of the matrix containing the first resin and the domain containing the second resin is formed. For example, when a twin-screw kneader is used in the melting and kneading step, a mechanism for applying shear stress to the discharged melted and kneaded material may be provided.

[0075] As a mechanism for applying shear stress to the molten kneaded material, when the molten kneaded material is cooled and solidified, it is preferable to cool it after rolling or to roll it while cooling it. As a method for cooling after rolling, a method of rolling with a press roller and then cooling with a steel belt cooler can be mentioned. As a method for rolling while cooling, a method of simultaneously cooling and rolling with a press roller having a cooling mechanism can be mentioned. By rolling, it becomes easier to align the orientation of the domains and maintain that state by cooling. That is, in the toner manufacturing method, when the molten kneaded material is cooled and solidified, it is preferable to roll it while cooling it. is preferred.

[0076] In addition, the first resin and the second resin are preferably a combination in which the first resin and the second resin are incompatible when the mixture of the first resin and the second resin is melt-kneaded at 150°C and observed at 150°C. By using a combination of resins that are incompatible at high temperatures, it becomes easier to apply shear stress and to align the domain orientation. Specifically, the observation of the melt-kneaded product at 150°C is performed as follows. The melt-kneaded product obtained by melt-kneading the mixture of the first resin and the second resin at 150°C with a twin-screw kneader is heated to 150°C on a hot plate and observed. If the melt-kneaded product is opaque in the observation, it is determined that the two resins are incompatible.

[0077] The procedure for producing the toner using the melt-kneading pulverization method will be described below. <Raw material mixing process> In the raw material mixing process, materials constituting the toner particles, such as binder resin, release agent, and other components such as colorant and charge control agent as necessary, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include double con mixers, V-type mixers, drum mixers, super mixers, Henschel mixers, Nauta mixers, and Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.).

[0078] <Melting and kneading process> Next, the mixed materials are melt-kneaded to disperse the release agent in the binder resin. In the melt-kneading process, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used, and single-screw or twin-screw extruders are mainstream due to their advantage of continuous production. For example, a KTK twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned. Furthermore, the resin composition obtained by melt-kneading may be rolled with two rolls or the like and cooled with water or the like in a cooling process.

[0079] In particular, it is preferable to roll the resin composition after melt kneading and then rapidly cool the resin composition immediately thereafter, since this makes it easier to control the orientation degree of the domains within the above-mentioned specific range. Examples of such methods include a method in which the resin composition after melt kneading is rolled with two rollers or drums and then cooled with a steel belt cooler (manufactured by Nippon Steel Conveyor Co., Ltd.), or a method in which the resin composition is rolled while being cooled with a press roller and a drum equipped with a cooling mechanism inside, such as a belt drum flaker (manufactured by Nippon Coke Co., Ltd.). A preferred method is to roll the resin composition after melt kneading while being cooled with a press roller and a drum equipped with a cooling mechanism inside.

[0080] In order to control the orientation of the domains, the melt-kneaded resin composition is preferably cooled at a high cooling rate to a temperature below the melting point Tp of the first resin, and the time required to cool to a temperature below the Tp of the first resin is preferably short. The time required for the melt-kneaded resin composition to be rolled and cooled to a temperature below the melting point Tp of the first resin after melting is preferably within 30 seconds, more preferably within 20 seconds, and even more preferably within 15 seconds. The cooling rate from rolling to a temperature below the melting point Tp of the first resin is preferably 3°C / sec to 50°C / sec, more preferably 4°C / sec to 30°C / sec, and even more preferably 5°C / sec to 12°C / sec. The dispersion state of the first resin and the second resin, the average major axis of the domains, and the like can be controlled by the kneading temperature in the melt-kneading step, the number of rotations of the screw, and the like.

[0081] <Crushing process> Next, the cooled resin composition is pulverized to a desired particle size in a pulverization step. In the pulverization step, for example, the resin composition is coarsely pulverized with a pulverizer such as a crusher, a hammer mill, or a feather mill, and then crushed into a desired particle size. The mixture is then pulverized using a mill such as a Cryptron System (Kawasaki Heavy Industries), a Super Rotor (Nisshin Engineering), a Turbo Mill (Turbo Kogyo), or an air jet type mill.

[0082] <Classification process> Thereafter, as necessary, the mixture is classified using a classifier or sieve such as an inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), or a Faculty (manufactured by Hosokawa Micron Corporation).

[0083] <External addition process> The obtained toner particles may be used as a toner as it is. If necessary, an external additive may be added to the surface of the toner particles to form a toner. As a method for adding an external additive, a method may be mentioned in which the classified toner and various known external additives are mixed in a predetermined amount, and stirred and mixed using a mixing device such as a double con mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation) as an external additive machine.

[0084] <Evaluation of domain matrix structure by cross-sectional observation of toner> First, a thin sample was prepared as a reference sample for the amount of the metal. The first resin, which is a crystalline resin, is thoroughly dispersed in a viscoelastic dispersion liquid (LCR Series D800), and then irradiated with short-wavelength light to harden it. The hardened material obtained is cut with an ultramicrotome equipped with a diamond knife to prepare a 250 nm thin sample. In the same manner, a thin sample is also prepared for the second resin, which is an amorphous resin.

[0085] In addition, the first resin and the second resin are mixed at 30 / 70 and 70 / 30 by mass, and melt-kneaded to prepare a kneaded product. These are also dispersed in a visible light curable resin, cured, and then cut out to prepare thin-section samples. Next, the cut-out samples are observed at the cross section of these reference samples using a transmission electron microscope (JEM-2800 electron microscope manufactured by JEOL Ltd.) (TEM-EDX), and element mapping is performed using EDX. The elements to be mapped are carbon, oxygen, and nitrogen. The mapping conditions are as follows: Accelerating voltage: 200 kV Electron beam irradiation size: 1.5 nm Live time limit: 600sec Dead time: 20~30 Mapping resolution: 256×256

[0086] Based on the spectral intensity (average in an area of ​​10 nm square) of each element, calculate (oxygen element intensity / carbon element intensity) and (nitrogen element intensity / carbon element intensity) and create a calibration curve for the mass ratio of the first resin to the second resin. If the monomer unit of the first resin contains nitrogen atoms, the calibration curve of (nitrogen element intensity / carbon element intensity) will be used for future quantification.

[0087] Next, the toner sample is analyzed. After thoroughly dispersing the toner in a visible light curable resin (Aronix LCR Series D800), it is irradiated with short wavelength light and cured. The resulting cured product is cut out using an ultramicrotome equipped with a diamond knife to prepare a 250 nm thin sample. The cut sample is then observed using a transmission electron microscope (JEOL JEM-2800) (TEM-EDX). Cross-sectional images of the toner particles are obtained, and elemental mapping is performed using EDX. The elements to be mapped are carbon, oxygen, and nitrogen.

[0088] The toner particle cross section to be observed is selected as follows. First, the cross-sectional area of ​​the toner particle is obtained from the toner particle cross-sectional image, and the diameter (equivalent circle diameter) of a circle having an area equal to the cross-sectional area is obtained. Only toner particle cross-sectional images in which the absolute value of the difference between this equivalent circle diameter and the weight average particle diameter (D4) of the toner particle is within 1.0 μm are observed. For the domains confirmed in the observed image, (oxygen element intensity / carbon element intensity) and / or (nitrogen element intensity / carbon element intensity) are calculated based on the (average of 10 nm square) spectral intensity of each element, and the ratio of the first resin to the second resin is calculated by comparing with the calibration curve. Domains in which the ratio of the second resin is 80% or more are defined as domains of the present disclosure.

[0089] When the ratio of the toner particle cross section forming a matrix domain structure among the toner particle cross sections is 80% by number or more, the toner particle cross section of the toner to be measured is determined to have a matrix domain structure. The matrix domain structure is a state in which domains, which are discontinuous phases, are dispersed in a matrix, which is a continuous phase. Here, the continuous phase means that, in the toner particle cross section, when 90% or more of the area of ​​the first resin or the area occupied by the second resin exists as one continuous region, the first resin or the second resin is determined to be a continuous phase.

[0090] After identifying the domains confirmed by the observed image, a binarization process is performed. The binarized image is analyzed to determine the domain major axis La present in the cross-sectional image of the toner particle, the angle of the domain in the longitudinal direction, and the maximum length Lb in the direction perpendicular to the major axis La of the domain. This is measured at 10 points per toner particle, and the arithmetic average value of the domain major axes La of the 10 toner particles is regarded as the average major axis (μm) of the domain. The longitudinal direction of the domain is the longest direction of the domain. In other words, it is the direction of the line segment that forms the major axis La.

[0091] On the other hand, the standard deviation of the longitudinal angle of the domain is calculated by the following method. First, an arbitrary reference axis (vertical or horizontal axis of the SEM photograph) is set, and the angle between the reference axis and the longitudinal direction of each of the 10 domains in one toner particle is measured. This is defined as the longitudinal angle of the domain. The average value of the longitudinal angles of the 10 domains measured for each toner particle is calculated, and the angle is calculated by subtracting the average value from the measured value. This operation is performed for 10 toner particles, and the standard deviation is calculated based on the angle data of 100 pieces, which is defined as the standard deviation of the longitudinal angle of the domain. In addition, the La / Lb value is calculated for each domain, and the arithmetic average of the 100 domains is defined as the La / Lb of the toner particle.

[0092] Meanwhile, the area of ​​the domains is calculated by adding up the areas of all the domains present in one toner particle cross-sectional image to obtain the total area, which is designated as S1. The total area of ​​the domains of 100 toner particles (i.e., S1 + S2... + S100) is calculated, and the arithmetic average value of the 100 particles is designated as the "domain area."

[0093] Regarding the cross-sectional area of ​​the toner particles, the sum of the cross-sectional areas of the toner particles (100 toner particles) calculated from the toner cross-sectional images used to calculate the area of ​​the domains is calculated, and the arithmetic average value is taken as the "total cross-sectional area of ​​the toner particles." The "total cross-sectional area of ​​the toner particles" minus the "area of ​​the domain" is taken as the "area of ​​the matrix." The area ratio of the matrix to the total cross-sectional area of ​​the toner particles (area ratio of the matrix (%)) is then taken as the [area of ​​the matrix] / [total cross-sectional area of ​​the toner particles] x 100. The image processing software "ImageJ" is used for the binarization process and for calculating the average major axis of the domains and the standard deviation of the longitudinal angle of the domains.

[0094] In the image processing software, the major axis La can be selected from the Analyze menu > Analyze Particles > Fit Ellipse > Major. The maximum length Lb can be selected from the Analyze menu > Analyze The minor angle can be selected from the Analyze menu. This can be selected by >Analyze Particles>Fit Ellipse>Ma Angle.

[0095] <Method of separating each material from toner> By utilizing the difference in solubility of each material contained in the toner in a solvent, each material can be separated from the toner. First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and the soluble portion (second resin) is separated from the insoluble portion (first resin, release agent, colorant, inorganic fine particles, etc.). Second Separation: Dissolve the insoluble components (first resin, release agent, colorant, inorganic fine particles, etc.) obtained in the first separation in MEK at 100°C to separate the soluble components (first resin, release agent) and the insoluble components (colorant, inorganic fine particles, etc.). Third Separation: Dissolve the soluble components (first resin, release agent) obtained in the second separation in chloroform at 23°C to separate the soluble components (first resin) and the insoluble components (release agent).

[0096] (When including the third resin) First Separation: Dissolve the toner in methyl ethyl ketone (MEK) at 23°C to separate the soluble components (second resin, third resin) and the insoluble components (first resin, release agent, colorant, inorganic fine particles, etc.). Second Separation: Dissolve the soluble components (second resin, third resin) obtained in the first separation in toluene at 23°C to separate the soluble components (third resin) and the insoluble components (second resin). Third Separation: Dissolve the insoluble components (first resin, release agent, colorant, inorganic fine particles, etc.) obtained in the first separation in MEK at 100°C to separate the soluble components (first resin, release agent) and the insoluble components (colorant, inorganic fine particles, etc.). Fourth Separation: Dissolve the soluble components (first resin, release agent) obtained in the third separation in chloroform at 23°C to separate the soluble components (first resin) and the insoluble components (release agent).

[0097] (Measurement of the content of the first resin and the second resin in the binder resin in the toner) In each separation step obtained by the above separation, by measuring the mass of the soluble components and the insoluble components, the content of the first resin and the second resin in the binder resin in the toner is calculated. Also, the identification of the structure of the first resin separated from the toner, etc. 1 Known methods such as H-NMR can be adopted.

[0098] <Method for calculating the SP value> The SP value is calculated according to the calculation method proposed by Fedors as follows: For each polymerizable monomer, the vaporization energy (Δei) (cal / mol) and molar volume (Δvi) (cm) for the atom or atomic group in the molecular structure are calculated from the table in "Polym. Eng. Sci., 14(2), 147-154 (1974)". 3 / mol), (4.184×ΣΔei / ΣΔvi) 0.5 SP value (J / cm 3 ) 0.5 The SP value of a monomer unit is calculated in the same manner as above for an atom or atomic group in a molecular structure in which the double bond of a polymerizable monomer is cleaved by polymerization.

[0099] <Method for measuring weight average molecular weight (Mw) of resins, etc. using gel permeation chromatography (GPC)> The weight average molecular weight (Mw) of tetrahydrofuran (THF) soluble matter such as resin is measured by gel permeation chromatography (GPC) as follows. First, a sample such as resin is dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The obtained solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of the THF soluble component is about 0.8 mass %. This sample solution is used to perform measurements under the following conditions. Equipment: HLC8120 GPC (detector: RI) (Tosoh Corporation) Column: Shodex KF-801, 802, 803, 804, 805, 806, 807 (Showa Denko) Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Oven temperature: 40.0℃ Sample injection volume: 0.10 mL

[0100] In calculating the molecular weight of the sample, a molecular weight calibration curve prepared using standard polystyrene resins (product names: "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation) is used.

[0101] <Measuring method for melting point, endothermic peak and endothermic amount of resin, etc.> The melting point of resins, etc., as well as endothermic peaks and endothermic amounts, are measured using a DSC Q1000 (TA Measurements are performed using a 350 Hz FT-IR spectrometer (manufactured by Instruments) under the following conditions. Heating rate: 10℃ / min Measurement start temperature: 20℃ End of measurement temperature: 180℃ The melting points of indium and zinc are used to correct the temperature of the detector, and the heat of fusion of indium is used to correct the amount of heat. Specifically, approximately 5 mg of sample is precisely weighed and placed in an aluminum pan, and differential scanning calorimetry is performed. An empty silver pan is used as a reference. The peak temperature of the maximum endothermic peak in the first heating process is taken as the melting point. Note that the maximum endothermic peak is the peak with the largest amount of endothermic heat when there are multiple peaks. The amount of endothermic heat of the maximum endothermic peak is then calculated.

[0102] <Method of measuring resin softening point (Tm)> The softening point of the resin is measured using a constant load extrusion type capillary rheometer "Flow characteristic evaluation device Flow Tester CFT-500D" (manufactured by Shimadzu Corporation) according to the manual that comes with the device. With this device, a constant load is applied from above the measurement sample by a piston, while the measurement sample filled in a cylinder is heated and melted, and the molten measurement sample is extruded from a die at the bottom of the cylinder, and a flow curve showing the relationship between the piston descent amount and temperature at this time can be obtained. The "melting temperature in the 1 / 2 method" described in the manual that comes with the "Flow characteristic evaluation device Flow Tester CFT-500D" is taken as the softening point. The melting temperature in the 1 / 2 method is calculated as follows.

[0103] First, find 1 / 2 of the difference between the amount of piston descent at the time when the outflow ends (end of outflow, Smax) and the amount of piston descent at the time when the outflow starts (minimum point, Smin) (this is X. X=(Smax-Smin) / 2). Then, the temperature of the flow curve when the amount of piston descent is the sum of X and Smin is the melting temperature in the 1 / 2 method. The measurement sample is a cylindrical shape with a diameter of about 8 mm, compressed and molded at about 10 MPa for about 60 seconds using a tablet molding compressor (for example, NT-100H, manufactured by NPA Systems Co., Ltd.) in an environment of 25°C. Specific operations in the measurement are performed according to the manual attached to the device. The measurement conditions for CFT-500D are as follows. Test mode: Temperature rise method Starting temperature: 50℃ Achieved temperature: 200℃ Measurement interval: 1.0℃ Heating rate: 4.0℃ / min Piston cross-sectional area: 1.000cm 2 Test load (piston load): 10.0kgf / cm 2 (0.9807MPa) Preheat time: 300 seconds Die hole diameter: 1.0mm Die length: 1.0mm

[0104] <Method of measuring weight-average particle size (D4) of toner (particles)> The weight-average particle diameter (D4) of the toner (particles) is measured with a precision particle size distribution measuring device using the pore electrical resistance method, "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.), equipped with a 100 μm aperture tube, and the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.), for setting measurement conditions and analyzing measurement data, with an effective measurement channel count of 25,000, and the measurement data is analyzed and calculated. The electrolyte solution used for the measurement is one in which special grade sodium chloride is dissolved in ion-exchanged water to a concentration of approximately 1 mass%, for example, "ISOTON II" (manufactured by Beckman Coulter, Inc.). Before performing the measurement and analysis, the dedicated software is set up as follows.

[0105] In the "Change Standard Measurement Method (SOM) Screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (manufactured by Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement. In the "Pulse to Particle Size Conversion Setting Screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bin, and the particle size range to 2 μm to 60 μm. The specific measurement method is as follows.

[0106] (1) Pour about 200 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture Tube Flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) Approximately 30 mL of the electrolyte solution is placed in a 100 mL flat-bottom glass beaker, and approximately 0.3 mL of a solution prepared by diluting "Contaminon N" (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7 consisting of a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) three times by weight with ion-exchanged water is added as a dispersant. (3) A specified amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 mL of Conaminon N is added to this water tank. (4) Set the beaker (2) in the beaker fixing hole of the ultrasonic disperser, operate the ultrasonic disperser, and adjust the height of the beaker so that the resonance state of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner (particles) is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, add the electrolytic solution (5) in which the toner (particles) is dispersed to the round-bottom beaker (1) placed in the sample stand, and adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight average particle size (D4) is calculated. Note that the analysis / volume statistical value (arithmetic mean) when the dedicated software is set to graph / volume% is The "average diameter" on the "average" screen is the weight average particle diameter (D4). EXAMPLES

[0107] The basic configuration and features of the present invention have been described above, and the present invention will be specifically described below based on examples. However, the present invention is not limited to these. Note that parts and % are based on mass unless otherwise specified.

[0108] <Production Example of First Resin 1 (Crystalline Resin 1)> Solvent: toluene 100.0 parts Monomer composition 100.0 parts (The monomer composition is a mixture of behenyl acrylate, acrylonitrile, and styrene in the ratio shown below.) (Behenyl acrylate 60.0 parts) (Acrylonitrile 10.0 parts) (27.5 parts styrene) Polymerization initiator 0.5 parts [t-Butyl peroxypivalate (NOF Corp.: Perbutyl PV)]

[0109] The above materials were put into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. The reaction vessel was heated to 70°C while stirring at 200 rpm, and a polymerization reaction was carried out for 12 hours to obtain a solution in which the polymer of the monomer composition was dissolved in toluene. The solution was then cooled to 25°C, and then the solution was poured into 1000.0 parts of methanol while stirring, to precipitate the methanol insoluble matter. The obtained methanol insoluble matter was filtered, washed with methanol, and then vacuum dried at 40°C for 24 hours to obtain a first resin 1 (crystalline resin 1). The weight average molecular weight (Mw) of the first resin 1 (crystalline resin 1) was 34,000, and the melting point (Tp) was 61°C.

[0110] When the first resin 1 (crystalline resin 1) was analyzed by NMR, it was found to contain 60.0 parts of monomer units derived from behenyl acrylate, 10.0 parts of monomer units derived from acrylonitrile, and 27.5 parts of monomer units derived from styrene in a mass ratio. The SP value (unit: (J / cm 3 ) 0.5 ) was calculated.

[0111] <Production Examples of First Resins 2 to 9 (Crystalline Resins 2 to 9)> In the production example of the first resin 1 (crystalline resin 1), the reaction was carried out in the same manner except that the respective monomers and the mass parts were changed as shown in Table 1, to obtain the first resins 2 to 9 (crystalline resins 2 to 9).

[0112] [Table 1]

[0113] The abbreviations in Table 1 are as follows. The numbers in parentheses indicate the SP value (J / cm) when the monomer unit was formed. 3 ) 0.5 It is. BEA: Behenyl acrylate (SP value: 18.3) SA: Stearyl acrylate (SP value: 18.4) MYA: Myrisil acrylate (SP value: 18.1) GEA: Gedyl acrylate (SP value: 18.0) AN: Acrylonitrile (SP value: 29.4) AA: Acrylic acid (SP value: 28.7) MN: Methacrylonitrile (SP value: 27.5) St: Styrene (SP value: 20.1)

[0114] <Production Example of First Resin 10 (Crystalline Resin 10)> 1,12-dodecanediol: 46.5 parts Dodecanedioic acid: 53.3 parts Tin 2-ethylhexanoate: 0.5 parts The above materials were weighed into a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. After replacing the inside of the flask with nitrogen gas, the temperature was gradually raised while stirring, and the reaction was carried out for 3 hours while stirring at a temperature of 140°C. Next, the pressure in the reaction vessel was reduced to 8.3 kPa, and the reaction was carried out for 4 hours while maintaining the temperature at 200°C. After that, the pressure in the reaction vessel was reduced to 5 kPa or less, and the reaction was carried out at 200°C for 3 hours to obtain crystalline resin 10.

[0115] <Production Example of Second Resin 1 (Amorphous Resin 1)> 50.0 parts of xylene was charged into the autoclave, and after replacing with nitrogen, the temperature was raised to 185 ° C. in a sealed state under stirring. A mixed solution of 80.7 parts of styrene, 17.8 parts of n-butyl acrylate, 1.1 parts of divinylbenzene, and 0.5 parts of acrylic acid, as well as 1.5 parts of di-tert-butyl peroxide and 20.0 parts of xylene was continuously dropped into the autoclave for 3 hours while controlling the temperature inside the autoclave to 185 ° C., and polymerization was performed. The temperature was further maintained for 1 hour to complete the polymerization, and the solvent was removed to obtain a second resin 1 (amorphous resin 1). The weight average molecular weight (Mw) of the second resin 1 (amorphous resin 1) was 40,000, and the softening point (Tm) was 100 ° C.

[0116] <Production Example of Second Resin 2 (Amorphous Resin 2)> In the production example of the second resin 1 (amorphous resin 1), the reaction was carried out in the same manner except that the amount of di-tert-butyl peroxide was changed from 1.5 parts to 4.0 parts, and the second resin 2 was obtained. The second resin 2 (amorphous resin 2) had a weight average molecular weight (Mw) of 15,000 and a softening point (Tm) of 70°C.

[0117] <Production Example of Second Resin 3 (Amorphous Resin 3)> In the production example of the second resin 1 (amorphous resin 1), the reaction was carried out in the same manner except that the number of parts of di-tert-butyl peroxide was changed from 1.5 parts to 5.0 parts, to obtain a second resin 3 (amorphous resin 3). The weight average molecular weight (Mw) of the second resin 3 (amorphous resin 3) was 10,000, and the softening point (Tm) was 65°C.

[0118] <Production Example of Second Resin 4 (Amorphous Resin 4)> (Polyester resin 1 formulation) Bisphenol A ethylene oxide (2.2 mol adduct) 50.0 mol parts Bisphenol A propylene oxide (2.2 mol adduct) 50.0 mol parts Terephthalic acid 65.0 mol parts Trimellitic anhydride 25.0 mol parts Acrylic acid 10.0 mol parts 90 parts of the mixture of monomers that produce the polyester resin 1 was charged into a four-neck flask, and the flask was equipped with a pressure reducing device, a water separator, a nitrogen gas introducing device, a temperature measuring device, and a stirrer, and stirred at 160 ° C. under a nitrogen atmosphere. 10 parts of vinyl polymerizable monomers that produce vinyl resins (styrene 81.0 parts, acrylate-n-butyl 17.0 parts, acrylic acid 0.9 parts, divinylbenzene 1.1 parts) and 1 part of benzoyl peroxide as a polymerization initiator were dropped from a dropping funnel over 4 hours, and reacted at 160 ° C. for 5 hours. The mixture was then heated to 230 ° C., and 0.2 parts of titanium tetrabutoxide was added relative to the total amount of monomers that produce the polyester resin, and polymerization was carried out until the softening point reached 115 ° C. After the reaction was completed, the mixture was removed from the vessel, cooled, and pulverized to obtain a second resin 4 (amorphous resin 4).

[0119] <Toner 1 Manufacturing Example> ·Crystalline resin 1 50.0 parts Amorphous resin 1 50.0 parts 5.0 parts wax 1 (Fischer-Tropsch wax; melting point 90°C) Colorant 1 9.0 parts (Cyan pigment made by Dainichi Seika: Pigment Blue 15:3) The above materials were mixed in a Henschel mixer (FM-75, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 20 s -1 After mixing for 5 min, the mixture was kneaded in a twin-screw kneader (PCM-30, Ikegai Corporation) set at a temperature of 130°C, with a screw rotation speed of 250 rpm and a discharge temperature of 130°C. The kneaded product obtained was rolled while being cooled using a drum flaker (MBD30-30, Nippon Coke Corporation). The temperature of the cooling water was set at 15°C, and the conditions were set so that the thickness of the resin composition after rolling and cooling would be 1.0 mm. The time required for the temperature to drop below the melting point Tp of the first resin after melting was (10 seconds), and the cooling rate from rolling to the melting point Tp of the first resin was (7°C / second).

[0120] The mixture was coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed product. The obtained coarsely crushed product was finely crushed using a mechanical crusher (T-250, manufactured by Freund Turbo Co., Ltd.). It was then classified using a Faculty F-300 (manufactured by Hosokawa Micron Co., Ltd.) to obtain toner particles 1 having a weight average particle size of about 6.0 μm. The operating conditions were a classifying rotor rotation speed of 130 s -1 , Dispersion rotor speed 120s -1 It was decided.

[0121] For 100 parts of toner particles, the surface is treated with 4% by mass of hexamethyldisilazane to obtain a BET specific surface area of ​​25 m 2 / g hydrophobic silica fine particles 0.5 parts, polydimethylsiloxane 10 parts Surface treatment BET specific surface area 100m 2 0.5 parts of hydrophobic silica particles / g were added, and the mixture was mixed in a Henschel mixer (FM-75, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 30 s -1 The mixture was mixed for 10 minutes at 40° C. and rotated to obtain toner 1. Based on the above-mentioned method, the cross section of the produced toner 1 was observed, and the domain matrix structure, the average major axis of the domain, the standard deviation of the angle in the longitudinal direction of the domain, and La / Lb were evaluated. The results are shown in Table 3.

[0122] <Production examples of toners 2, 6-8, 23-28> Toners 2, 6 to 8, and 23 to 28 were obtained by the same production procedure as in Production Example of Toner 1, except that the first resin and the second resin were changed to the resins shown in Table 2. The evaluation results of Toners 2, 6 to 8, and 23 to 28 are shown in Table 3.

[0123] <Production Example of Toners 3 to 5> Toners 3 to 5 were obtained by carrying out the same production procedure as in the production example of toner 1, except that the cooling water temperature during rolling and cooling was changed to the conditions shown in Table 2. The evaluation results of toners 3 to 5 are shown in Table 3.

[0124] <Production Example of Toner 9 to 14> Toner particles 9 to 14 were obtained by carrying out the same production procedure as in the production example of toner 1, except that the ratio of the first resin to the second resin was changed to the conditions shown in Table 2. The evaluation results of toners 9 to 14 are shown in Table 3.

[0125] <Production example of toner 15 and 16> Toners 15 and 16 were obtained by carrying out the same production procedure as in the production example of toner 1, except that the second resin was changed to the resin shown in Table 2 and wax 1 was changed to wax 2 shown below. 5.0 parts Wax 2 (Microcrystalline wax; melting point 65°C) The evaluation results of Toners 15 and 16 are shown in Table 3.

[0126] <Production Example of Toner 17-22> Toners 17 to 22 were obtained in the same manner as in the production example of toner 1, except that the screw rotation speed and discharge temperature were changed as the operating conditions of the twin-screw kneader (PCM-30 type, manufactured by Ikegai Corporation) to the conditions shown in Table 2. The evaluation results of toners 17 to 22 are shown in Table 3.

[0127] [Table 2] In the toners in Table 2 except for Toner 26, the crystalline resin and the amorphous resin used were incompatible when the melt-kneaded product was melt-kneaded at 150°C and observed at 150°C.

[0128] <Toner 29 Manufacturing Example> Toner 29 was produced by emulsion polymerization. First, each dispersion was produced by the method described below.

[0129] <Production example of crystalline resin 1 fine particle dispersion> Toluene (Wako Pure Chemical Industries, Ltd.) 300 parts ·Crystalline resin 1 100 parts The above materials were weighed, mixed, and dissolved at 100° C. Separately, 5.0 parts of sodium dodecylbenzenesulfonate and 10.0 parts of sodium laurate were added to 700 parts of ion-exchanged water. The mixture was heated and dissolved at 100°C. The toluene solution and the aqueous solution were then mixed and stirred at 7000 rpm using an ultra-high speed stirring device TK Robomix (manufactured by Primix). The mixture was then emulsified at a pressure of 200 MPa using a high-pressure impact disperser Nanomizer (manufactured by Yoshida Kikai Kogyo). After that, the toluene was removed using an evaporator, and the concentration was adjusted with ion-exchanged water to obtain an aqueous dispersion (crystalline resin fine particle 1 dispersion) with a concentration of 20% by mass of crystalline resin 1 fine particles. The 50% particle size (D50) based on the volume distribution of crystalline resin 1 was measured using a dynamic light scattering particle size distribution meter Nanotrac UPA-EX150 (manufactured by Nikkiso), and was found to be 0.40 μm.

[0130] <Production example of amorphous resin 1 fine particle dispersion> Tetrahydrofuran (Wako Pure Chemical Industries, Ltd.) 300 parts 100 parts of amorphous resin 1 Anionic surfactant Neogen RK (Daiichi Kogyo Seiyaku) 0.5 parts The above materials were weighed, mixed, and dissolved. Then, 20.0 parts of 1 mol / L ammonia water was added, and the mixture was stirred at 4000 rpm using an ultra-high speed stirring device TK Robomix (manufactured by Primix). Furthermore, 700 parts of ion-exchanged water was added at a rate of 8 g / min to precipitate amorphous resin 1 fine particles. Then, tetrahydrofuran was removed using an evaporator, and the concentration was adjusted with ion-exchanged water to obtain an aqueous dispersion (amorphous resin 1 fine particle dispersion) with a concentration of amorphous resin 1 fine particles of 20 mass%. The 50% particle diameter (D50) based on volume distribution of the amorphous resin 1 fine particles was 0.14 μm.

[0131] <Production Example of Wax Particle Dispersion> Wax 1 100.0 parts (Fischer-Tropsch wax; maximum endothermic peak temperature 90℃) Anionic surfactant Neogen RK (manufactured by Daiichi Kogyo Seiyaku) 5 parts 395 parts of ion-exchanged water The above materials were weighed and placed in a mixing vessel equipped with an agitator, then heated to 90°C and circulated through a Clearmix W Motion (manufactured by M Technique) for 60 minutes to perform dispersion processing. The dispersion processing conditions were as follows: Rotor outer diameter: 3cm Clearance: 0.3mm Rotor speed: 19000 r / min Screen rotation speed: 19000 r / min

[0132] After the dispersion process, the mixture was cooled to 40°C under the following cooling conditions: rotor rotation speed 1000 r / min, screen rotation speed 0 r / min, and cooling rate 10°C / min, to obtain an aqueous dispersion of wax microparticles with a concentration of 20% by mass (wax microparticle dispersion). The 50% particle size (D50) based on volume distribution of the wax microparticles was measured using a dynamic light scattering particle size distribution analyzer Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.15 μm.

[0133] <Production Example of Colorant Microparticle Dispersion> Colorant 1 50.0 parts (Cyan pigment made by Dainichi Seika: Pigment Blue 15:3) Anionic surfactant Neogen RK (manufactured by Daiichi Kogyo Seiyaku) 7.5 parts 442.5 parts ion-exchanged water The above materials were weighed, mixed, dissolved, and dispersed for about 1 hour using a high-pressure impact disperser Nanomizer (manufactured by Yoshida Kikai Kogyo Co., Ltd.) to obtain a water-based dispersion of colorant particles with a concentration of 10% by mass (colorant particle dispersion liquid). The 50% particle size (D50) based on the volume distribution of the colorant particles was measured using a dynamic light scattering particle size distribution meter Nanotrac UPA-EX150 (manufactured by Nikkiso Co., Ltd.) and found to be 0.20 μm.

[0134] Using each of the dispersions prepared by the above methods, toner particles were prepared by the following method. <Toner particle manufacturing example> ·Crystalline resin 1 fine particle dispersion 50.0 parts ·Amorphous resin 1 fine particle dispersion 50.0 parts Wax microparticle dispersion 5.0 parts Colorant fine particle dispersion 9.0 parts 20.0 parts ion-exchanged water Crystalline resin for post-treatment 1 fine particle dispersion 3.0 parts

[0135] All the materials except for the post-treatment crystalline resin 1 fine particle dispersion were put into a round stainless steel flask and mixed. Then, the homogenizer Ultra Turrax T50 (IKA) was used to disperse the mixture at 5000 r / min for 10 minutes. After adding a 1.0% nitric acid aqueous solution and adjusting the pH to 3.0, the mixture was heated to 58°C in a heating water bath using a stirring blade while appropriately adjusting the rotation speed so that the mixture was stirred. The formed aggregated particles were appropriately confirmed using a Coulter Multisizer III, and the mixture was held until the weight average particle size (D4) reached about 6.4 μm. After that, the post-treatment crystalline resin 1 fine particle dispersion was added, and the mixture was held for another 30 minutes, and then the pH was adjusted to 9.0 using a 5% sodium hydroxide aqueous solution.

[0136] Then, while continuing stirring, the mixture was heated to 75°C. The mixture was then held at 75°C for 1 hour to fuse the aggregated particles. The mixture was then cooled to 50°C and held for 3 hours to promote crystallization of the resin. The mixture was then cooled to 25°C, filtered and separated into solid and liquid, thoroughly washed with ion-exchanged water, and dried to obtain toner particles 29. The toner particles 29 were subjected to the same external addition treatment as toner 1 to obtain toner 29. The weight average particle size (D4) of toner 29 was about 6.0 μm. The evaluation results of toner 29 are shown in Table 3.

[0137] [Table 3] The area ratio of the matrix of the toner particle 9 is the area ratio when the matrix is ​​an amorphous resin. "Standard deviation of domain angle" indicates the standard deviation of the angle of the domain in the longitudinal direction.

[0138] <Magnetic Carrier 1 Manufacturing Example> Number average particle size: 0.30μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 1 Number average particle size: 0.50μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 2 To 100 parts of each of the above materials, 4.0 parts of a silane compound (3-(2-aminoethylaminopropyl)trimethoxysilane) was added, and the mixture was mixed and stirred at high speed in a container at 100° C. or higher to treat each of the fine particles.

[0139] Phenol: 10% by weight Formaldehyde solution: 6% by mass (40% by mass of formaldehyde, 10% by mass of methanol, 50% by mass of water) Magnetite treated with the above silane compound 1:58 mass% Magnetite treated with the above silane compound 2: 26% by mass 100 parts of the above material, 5 parts of 28% by mass aqueous ammonia, and 20 parts of water were placed in a flask, and the temperature was raised to 85°C in 30 minutes and held while stirring and mixing, and polymerization reaction was carried out for 3 hours to harden the resulting phenolic resin. The hardened phenolic resin was then cooled to 30°C, and water was added, after which the supernatant liquid was removed, and the precipitate was washed with water and then air-dried. This was then dried at a temperature of 60°C under reduced pressure (5 mmHg or less) to obtain a spherical magnetic carrier 1 with magnetic material dispersion. The 50% particle size (D50) based on volume of the magnetic carrier 1 was 34.2 μm.

[0140] <Production example of two-component developer 1> Toner 1 (8.0 parts) was added to magnetic carrier 1 (92.0 parts), and mixed in a V-type mixer (V-20, manufactured by Seishin Enterprises) to obtain two-component developer 1.

[0141] <Production Examples of Two-Component Developers 2 to 29> Two-component developers 2 to 29 were obtained by carrying out the same production procedure as in the production example of two-component developer 1, except that toner 1 was changed to toners 2 to 29, respectively.

[0142] <Example 1> The evaluation was performed using the above two-component developer 1. A modified Canon digital commercial printing printer imageRUNNER ADVANCE C5560 was used as the image forming apparatus, and two-component developer 1 was placed in the cyan developer. The device was modified so that the fixing temperature, process speed, direct current voltage VDC of the developer carrier, charging voltage VD of the electrostatic latent image carrier, and laser power could be freely set. The image output evaluation was performed by outputting an FFh image (solid image) with a desired image ratio, adjusting VDC, VD, and laser power so that the amount of toner on the FFh image on the paper was desired, and performing the evaluation described below. FFh is a value that expresses 256 gradations in hexadecimal, where 00h is the first gradation (white background) of the 256 gradations, and FFh is the 256th gradation (solid portion) of the 256 gradations. Evaluation was performed based on the following evaluation method, and the results are shown in Table 4.

[0143] <Low temperature fixability> ·Paper: GFC-081 (81.0g / m 2 ) (Sold by Canon Marketing Japan Inc.) Toner load on paper: 0.70mg / cm 2 (Adjusted by DC voltage VDC of developer carrier, charging voltage VD of electrostatic latent image carrier, and laser power) Evaluation image: Place a 2cm x 5cm image in the center of the A4 paper. Test environment: Low temperature and low humidity environment: Temperature 15℃ / Humidity 10%RH (hereinafter referred to as "L / L") Fixing temperature: 140℃ Process speed: 400mm / sec

[0144] The above evaluation image was output, and the low-temperature fixability was evaluated. The value of the image density reduction rate was used as an evaluation index for the low-temperature fixability. The image density reduction rate was measured using an X-Rite color reflection densitometer (500 series: manufactured by X-Rite Corporation) by first measuring the image density at the center. Next, the part where the image density was measured was subjected to pressure of 4.9 kPa (50 g / cm 2The fixed image was rubbed (five times back and forth) with Silbon paper under a load of 1000 g / m2, and the image density was measured again. The image density reduction rate before and after the rub was calculated using the following formula. The obtained image density reduction rate was evaluated according to the following evaluation criteria. Image density decrease rate=(image density before friction−image density after friction) / (image density before friction)×100 (Evaluation Criteria) AA: Image density reduction rate is less than 1.0% A: Image density reduction rate: 1.0% to less than 3.0% B: Image density reduction rate: 3.0% or more and less than 5.0% C: Image density reduction rate: 5.0% or more and less than 8.0% D: Image density reduction rate 8.0% or more

[0145] <Fixation separation property> ·Paper:CS-052(52.0g / m 2 ) (Sold by Canon Marketing Japan Inc.) Toner load on paper: 0.60mg / cm 2 (Adjusted by DC voltage VDC of developer carrier, charging voltage VD of electrostatic latent image carrier, and laser power) Evaluation image: A 2cm x 20cm image is placed on the long edge of the A4 paper with a margin of 1.5mm from the leading edge of the paper. Test environment: High temperature and humidity environment: Temperature 30℃ / Humidity 80%RH (hereinafter referred to as "H / H") Fixing temperature: 140℃ to 5℃ increments Process speed: 400mm / sec The above evaluation image was output, and the winding resistance was evaluated according to the following criteria at the highest fixing temperature at which winding did not occur. (Evaluation Criteria) AA: 175℃ or higher A: 165℃ or higher and lower than 175℃ B: 155℃ or higher and less than 165℃ C: 145℃ or higher but lower than 155℃ D: Less than 145℃

[0146] <Examples 2 to 24 and Comparative Examples 1 to 5> Evaluation was carried out in the same manner as in Example 1, except that two-component developers 2 to 29 were used instead of two-component developer 1. The evaluation results are shown in Table 4.

[0147] [Table 4]

Claims

1. A toner having toner particles containing a binder resin and a release agent, The binder resin contains a first resin and a second resin, The first resin is a crystalline resin having a melting point Tp of 50° C. or more and 90° C. or less, the second resin is an amorphous resin, In a cross section of the toner particle observed by a transmission electron microscope, a matrix domain structure is present, which is composed of a matrix in which 90 area % or more of the area of ​​the first resin exists as one continuous region, and a domain in which the ratio of the second resin in the ratio of the first resin to the second resin calculated based on the spectrum intensity measured by TEM-EDX is 80% or more; the area ratio of the matrix to the total area of ​​the cross section of the toner particle is 35 area % or more and 70 area % or less; The toner is characterized in that, when the longest direction of the domain is taken as the longitudinal direction and an arbitrary reference axis is set on the cross section of the toner particle, the standard deviation of the angle between the reference axis and the longitudinal direction of the domain is 25° or less.

2. 2. The toner according to claim 1, wherein the softening temperature Tm of the second resin is higher than the melting point Tp of the first resin by 10[deg.] C. or more.

3. 3. The toner according to claim 1, wherein the matrix occupies 60% or less of the total area of ​​the cross section of the toner particle.

4. 4. The toner according to claim 1, wherein, upon cross-sectional observation of the toner, an average length of the domain in the longitudinal direction is 20 nm or more and 500 nm or less.

5. 5. The toner according to claim 1, wherein, upon cross-sectional observation of the toner, a ratio La / Lb of a length La of the domain in the longitudinal direction to a maximum length Lb in a direction perpendicular to the longitudinal direction is 8.0 or less.

6. 6. The toner according to claim 1, wherein the first resin has a first monomer unit represented by the following formula (1): [In formula (1), R Z1 represents a hydrogen atom or a methyl group, R 1 represents an alkyl group having 18 to 36 carbon atoms.

7. the first resin comprises a vinyl resin, 7. The toner according to claim 1, wherein the second resin comprises a styrene-acrylic resin.

8. The toner according to any one of claims 1 to 7, wherein the release agent comprises a hydrocarbon wax.

9. A method for producing the toner according to any one of claims 1 to 8, comprising the steps of: a melt-kneading step of melt-kneading a composition containing a binder resin including the first resin and the second resin, and the release agent to obtain a melt-kneaded product; and a grinding step of cooling and solidifying the molten kneaded product, and grinding the cooled and solidified product to obtain a ground product; The method for producing a toner comprises rolling the molten kneaded product while cooling it to solidify it.

10. A method for producing the toner according to claim 9, A method for producing a toner, wherein when a mixture of the first resin and the second resin is melt-kneaded at 150°C and a melt-kneaded product is observed at 150°C, the first resin and the second resin are incompatible with each other.

Citation Information

Patent Citations

  • Toner for electrostatic charge image development, and image forming apparatus

    JP2014048576A

  • Toner, developer, and image forming device

    JP2014059489A

  • Toner

    JP2014142632A

  • Toner binder

    JP2019214706A

  • Toner and method for manufacturing toner

    JP2019219643A